EVALUASI MEDIA BIMBINGAN KELOMPOK BERBASIS KESENIAN SINGO ULUNG DALAM MENINGKATKAN TANGGUNG JAWAB AKADEMIK SISWA - Aisah Fadilah; Weni Kurnia Rahmawati; Nailul Fauziyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low academic responsibility of seventh-grade students at MTs Nurul Fata is characterized by a lack of discipline, late submission of assignments, and low learning readiness. This problem indicates the need for more contextual guidance and counseling services in accordance with the needs and socio-cultural environment of students. This study aims to evaluate the Singo Ulung artistic value-based group guidance service module to improve the academic responsibility of seventh-grade students at MTs Nurul Fata Bondowoso. The method used is research and development with the stages of needs analysis, service planning, expert validation, and small group trials. The small group trial was conducted by providing group guidance services to six students using the Singo Ulung artistic value-based module, then students were asked to fill out a service response questionnaire. The research data were analyzed using descriptive statistical tests. The results of tests by media experts, cultural experts, and material experts showed that the Singo Ulung artistic value-based group guidance service module was in the very feasible category for use. The module was considered interesting, relevant to local cultural values, and appropriate for improving students' academic responsibility through group guidance services. The results of the small group test showed that the Singo Ulung artistic values-based group guidance service module received a positive response from students based on the results of the questionnaire given. Students considered the module interesting, easy to understand, and suitable for use in group guidance service activities. The Singo Ulung artistic values-based group guidance service is suitable for use as an alternative guidance and counseling service in schools. Thus, the Singo Ulung artistic values-based group guidance service received a positive response and has the potential to support the implementation of more contextual guidance and counseling services in Islamic boarding school environments.